MENINGKATKAN KEMAMPUAN HASIL BELAJAR MUATAN IPA MELALUI MODEL DISCOVERY LEARNING SISWA KELAS II SDN NGLUMBER 1: IMPROVING THE ABILITY OF LEARNING OUTCOMES OF SCIENCE CONTENT THROUGH THE DISCOVERY LEARNING MODEL OF GRADE II STUDENTS OF NGLUMBER 1 ELEMENTARY SCHOOL - Cahyani, Indah Wahyu Nur; Setyawan, Agung (CV. Kalimasada Group, 2023)
The poor learning outcomes of Grade 1 science students at SDN Number 1, where many students scored below the minimum competency standard (KKM), was the impetus behind this study. The discovery approach was seen as a substitute for improving these results, which has led to additional investigation into its efficacy. Finding out how many students benefit from using the discovery model to improve science learning outcomes is the goal of this project. Second graders participated in this classroom action research project, which collected data through observation sheets, assessments, and documentation. The findings show how the discovery model improved student achievement. Only 6 students (21%) met the requirements before implementation. This increased to 17 students (59%), and 26 students (90%) achieved proficiency in Cycle II. Thus, at SDN Number 1, the discovery approach successfully improved science learning outcomes.